INCREASING STUDENTS’ LEARNING ACTIVITY IN MEDIA AND LEARNING RESOURCES CLASS BY USING NUMBER HEADS TOGETHER (NHT) ( A CLASSROOM ACTION RESEARCH) - Maulida, Hidya; Norliani, Norliani (LET: Linguistics, Literature and English Teaching Journal, 2016)
This research aims to increase students? learning activity in Media and Learning Resources class. The kind of research is classroom action research conducted two cycles with the subject is the fifth semester students of English departement. Technique of collecting data is observation and analyzing quantitatively and qualitatively.  From cycle I and cycle II, students? learning activity is increasing . Research hypothes stated that the use of Number Heads Together technique can increase the students? learning activity can be proven. It is concluded that the use of Number Heads Together (NHT) can increase students? learning activity in Media and Learning Resources class. The students? learning activity increases 37,5% , from 25% to 62,5%.  Number Heads Together should be developed and applied in every education level because this technique makes students are more aware that they are observed so it stimulates them to be active.